Hydro-geomorphic assessment of Yabroud city In the Majjar Basin (Upper Qalamoun) (Damascus University Journal of arts and humanities sciences, 2024)
The city of Yabrud is exposed, during frequent periods, to dangerous floods, which enter from three Canyon’s surrounding it from the south and west: Qurayna, Eskafta, and Mashkouna. Its waters collect from the drainage basins located on both sides of the Wadi Al-Majjar stream, during the period between (November - February).Ten quantitative geomorpho-hydrological criteria were developed to determine the degree of risk of water basins in the formation of torrents that pass through the city of Yabroud, which are: area, length, surface slope, shape of the basin, amount of water drainage, density of numbers of water courses, density of lengths of water courses, ratio Likely convergence, the ovaries' exits are away from the city. They were ranked in order, from least dangerous to most dangerous, as follows: Asakfta, Ras al-Maarat, Mishkouna and Jubbah, Rose Asal..The city is overlooked from its southern and western sides by slopes varying in width and similar in shape. On top of them rest many rock blocks, specifically in the upper and middle sections. They are predominantly cubic in shape, distributed according to two patterns (accumulated - scattered), spatially compatible with the ends of torrent streams. Its locations are on rocky cliffs.The causes of the dangers (confirmed and potential), in addition to natural factors, were residents choosing unsafe sites for their urban, agricultural, and service expansion. The new neighborhoods occupied the bottoms of the valleys and the beds of their torrent streams, as in the gorges of the valleys: Qurayna, Iskafta, and Mishkouna. And below rockslides, as in the Kushal spring and Al-Shibl, on the western slope of Ras Maroun Mountain, Jabal Al-Aridh, and at the foot of Wadi Eskafta.Two applied maps were prepared, the first of which was devoted to solving the external problems that threaten the city, namely floods, through a system of dams and storage wells. The second included identifying dangerous and safe sites for urban and service expansion in the city, according to geomorpho-hydrological standards
Keywords: Yabroud; Evaluation-; Geomorphology; Almajjar